Prenatal Gross Morphometrical Study of Spleen in Kosali Cattle - A. Rajput; S. P. Ingole; D. Chaurasia; B. K. Dewangan; S. K. Deshmukh; A. K. Nag; S. K. Thakur (Indian Journal of Veterinary Anatomy, 2025)
The present study was conducted on 24 Kosali foeti to study prenatal gross morphometrical development of the spleen. Kosali is the newly registered native cattle breed of Chhattisgarh, India, mostly reared in villages on agricultural residue. As per the CRL,foeti were categorised into four groups with six foeti in each group i.e. Group I (below 20cm CRL), Group II (Above 20 up to 40 cm CRL), Group III (Above 40 up to 60 cm CRL) and group IV (Above 60 cm CRL). The shape of spleen was oval and elongated in all four groups. The colorof spleen varied from plum red in group I to bluish red in group IV. In group I, the spleen was directed straight dorsoventrally between twelfth to tenth rib and in group IV, spleen was directed obliquely downward and forward from tenth rib to five cm above the xiphoid cartilage.Weight of spleen increased 117 times from group I to group IV.The maximum length of spleen was increased 5.56 times and in percentage 456.06 from group I to group IV and was significant. The five times increase in width of spleen was recorded from group I to group IV and was significant. The location of hilus relative to maximum total length shifted dorsoventral from group I to group III.